The challenges of da'wah in the era of artificial intelligence - Efendi Efendi; Sofwan Sulaiman; Amaruddin Amaruddin (Institute of Computer Science (IOCS), 2026)
The rapid integration of artificial intelligence (AI) into religious communication has transformed the practice of digital da'wah, yet studies that comprehensively examine both its opportunities and ethical challenges from an Islamic communication perspective remain limited. This study aims to analyze the potential, challenges, and ethical implications of AI in digital da'wah while addressing this research gap by synthesizing current scholarly evidence. The novelty of this study lies in its integrative analysis that connects AI adoption, Islamic communication ethics, and strategies for sustainable digital da'wah. This study employed a qualitative approach using library research as its research design. Data was collected through a documentation study of peer-reviewed scholarly journal articles, books, conference proceedings, and other scientific documents relevant to the research topic. The selected literature was analyzed systematically using predefined inclusion criteria to ensure its relevance and credibility. Data analysis was conducted using the content analysis method through the stages of data reduction, categorization, interpretation, and conclusion drawing. The findings reveal that AI has considerable potential to expand access to religious information and enhance the effectiveness of digital da'wah. Nevertheless, AI also poses risks, including a crisis of religious authority, the dissemination of unverified information, the commercialization of da'wah, and the diminishing humanistic dimension of religious communication. Therefore, strengthening digital literacy, improving technological competencies among da'i (Islamic preachers), implementing Islamic communication ethics, and fostering collaboration between religious scholars and technology developers are essential to ensure that the utilization of AI remains aligned with Islamic values. These findings contribute to the growing discourse on AI in religious communication by providing a conceptual framework for integrating technological innovation with Islamic ethical principles, thereby offering practical and theoretical guidance for future digital da'wah initiatives.